Development and validation of the “Adjustment Disorder Scale for Medically Ill Patients - ETAM” - Zapata-Ospina, Juan Pablo; Rodríguez, Natalia; Rodríguez, Ayda Margarita; García-Valencia, Jenny; Jiménez-Benítez, Mercedes; Martínez-Ramos, Nicolás; Restrepo Bernal, Diana; Gallego, Ana Lucía; Gómez, Carolina; Tabares, Luis Fernando; Cardeño-Castro, Carlos; Aguirre-Acevedo, Daniel Camilo (Frontiers in Psychiatry, 2025)
BackgroundAdjustment disorder (AD) is common among medically ill patients, yet current evaluation methods do not address the specific characteristics in this population. This study aimed to develop a measurement scale for AD in medically ill patients in Colombia and to find evidence of its validity and reliability.MethodsThis was a scale development and validation study. In the first qualitative phase, items were developed. In the second phase, the content validity of each item was evaluated by patients and clinicians. In the third phase, structural validity, internal consistency, test-retest reliability, criterion validity, and convergent construct validity were assessed. Items were analyzed using a generalized partial credit model within an item response theory framework.ResultsThe Adjustment Disorder Scale for Medically Ill Patients (ETAM, for its acronym in Spanish) was developed, comprising 20 items that address the free description of stressful situations in the last 15 days and mental symptoms attributed to them. Evidence of content validity was found. The scale was administered to 512 medically ill patients, revealing a three-dimensional structure: 1) “AD Symptoms”, 2) “Impact on Self-Care”, and 3) “Impact on Desire to Live”. Internal consistency was adequate, with McDonald’s omega of 0.95 and Cronbach’s alpha between 0.82 and 0.92 for its dimensions. ETAM had high test-retest reliability (intraclass correlation coefficient of 0.98). Criterion validity evidence was obtained with an independent psychiatrist’s diagnosis, with an AUROC of 0.99, and convergent validity was consistent with hypotheses of correlation with other instruments with similar constructs. Discrimination and difficulty parameters were calculated for each item.ConclusionThe ETAM is a scale with evidence of validity and reliability that can be used for the diagnosis of AD in medically ill patients in Colombia.